Predictive accuracy of cervical cytology and colposcopy in diagnosing premalignant and malignant cervical lesions: A hospital-based study from the sub-Himalayan region of Indian subcontinent - Amrita Singhal; Rashmi Kaul Raina; Suresh Verma; Ashok Verma (Wolters Kluwer Medknow Publications, 2019)
Background: Cancer of the cervix is one of the most common cancers among women in India. The study aimed to detect the predictive accuracy of cytology and colposcopy in cervical cancer screening among Himachali married women who had a high risk for cervical cancer. Materials and Methods: This was a hospital-based cross-sectional study. Two hundred nonpregnant married women with a high risk for cervical cancer and attending the gynecology clinic of a tertiary care center of Himachal Pradesh were included in the study over a period of 1 year. A detail clinical history was taken, and examination was performed in all the cases. Papanicolaou (Pap) smears for cytological examination were taken in all the cases. Colposcopy was performed in all the cases, and cervical punch biopsy was taken in all the women with suspicious lesions on colposcopy. Bethesda classification system (2001) and the WHO classification of tumors of the uterine cervix (2003) were used for reporting cytology and histopathology, respectively. Results: The mean age of the women in the study is 38.6 ± 6.2 years. Pap was reported as negative for intraepithelial lesion or malignancy in 88.5%, inflammatory in 32.5%, low-grade squamous intraepithelial lesion (LSIL) in 5.5%, high-grade SIL (HSIL) in 2.5%, and atypical squamous cells of undetermined significance in 1%. In the current study, the diagnostic accuracy of Pap smear and colposcopy for LSIL was 79.4% and 73.5%, respectively. The diagnostic accuracy of Pap smear and colposcopy for HSIL was 100% and 91.3%, respectively. Conclusion: This study has established the utility of Pap smear cytology and colposcopy as a screening tool for the detection of normal as well as abnormal lesions while analyzing cervical pathology in patients with high risk of cervical cancer.